Effects of Maren Pills on the Intestinal Microflora and Short-Chain Fatty Acid Profile in Drug-Induced Slow Transit Constipation Model Rats - Zhan, Yu; Wen, Yong; Du, Li-juan; Wang, Xiao-xiang; Tang, Shi-yu; Kong, Peng-fei; Huang, Wei-guo; Tang, Xue-gui (Frontiers in Pharmacology, 2022)
Backgrouond: Slow transit constipation (STC) is becoming a common and frequently-occurring disease in today’s society, it’s necessary to explore the safe and effective treatment of STC. Method: Our study aimed to investigate whether the laxative effect of Maren pills (MRW) is associated with the regulation of intestinal flora and intestinal metabolism in the colon. The loperamide hydrochloride-induced STC rats received MRW intragastrically for 2 consecutive weeks to evaluate the laxative effect of MRW involving the regulation of intestinal flora, intestinal metabolism, and 5-HT signaling pathway. Intestinal flora was detected by 16s rDNA sequencing, intestinal metabolism of short chain fatty acids (SCFAs) was detected by HPLC, and the 5-HT signaling pathway was detected by WB, ELISA, immunofluorescence and immunohistochemical. Results: Our results revealed that the treatments with MRW not only increased the body weight, 24 h fecal number, 24 h wet fecal weight, 24 h dry fecal weight, fecal water content, and the intestinal propulsion rate but also increased the colonic goblet cells number, colonic Muc-2 protein expression, and the colonic mucus layer thickness in the STC model rats. Moreover, MRW activated the 5-HT pathway by increasing the levels of 5-HT, 5-HIAA, 5-HT4R, CFTR, cAMP, and PKA in the colon tissue of STC rats. The 16S rDNA sequencing results showed that MRW improved colonic microflora structure in the colonic contents of STC rats, mainly by the increase in Lactobacillus and the decrease in [Prevotella]. Finally, we found that MRW regulated the SCFAs metabolism in the colonic contents of the STC rats, mainly increasing the contents of acetic acid, propionic acid, and butyric acid, and the relative abundance of Lactobacillus was positively correlated with either content among acetic acid, propionic acid, and butyric acid. Conclusion: Our study further showed that MRW could improve the constipation of STC rats, and the mechanism may be through regulating intestinal flora structure, improving SCFAs.